THE EFFECT OF DIFFERENCES IN COMMERCIAL FEED DOSES ON ABSOLUTE WEIGHT GROWTH OF SANGKURIANG CATFISH (Clarias gariepinus Var.) SIZED 9-12 CM IN EXPERIMENTAL TANKS - Indah Alfiana; Muhajir Muhajir; Indra Wirawan (Universitas Mataram, 2025)
The Sangkuriang catfish (Clarias gariepinus var.) has the advantage of adapting quickly to new environments, has a relatively high nutritional content, is technically easier to cultivate, and has a short life cycle, allowing for quicker harvest. Furthermore, this fish offers a very profitable economic prospect. Seeds measuring 9-12 cm can minimize the risk of cultivation failure due to their more stable and uniform growth. In aquaculture, feed plays a vital role because it directly affects the growth rate and health of fish. Commercial feeds have a very complete and balanced nutritional composition. One important element in feeding management is feed dosage. If the feeding is overdosed, it can pollute the aquatic environment and vice versa if the deficiency can cause malnutrition. This study aims to determine the effect of commercial feed doses on the absolute weight growth of sangkuriang catfish measuring 9-12 cm in experimental tanks. This study used an experimental method with a Completely Randomized Design (CRD) consisting of 5 treatments and 5 replications. The treatment in this study was the provision of commercial feed with different doses. Treatment A; dose 3% of the weight of the test animal biomass, treatment B; dose 5% of the weight of the test animal biomass, treatment C; dose 7% of the weight of the test animal biomass, treatment D; dose 9%, of the weight of the test animal biomass and treatment E; dose 11% of the weight of the test animal biomass. The test animals used sangkuriang catfish measuring 9-12 cm with an average weight of 5 g/individual. The stocking density was 1 individual/liter, the experimental media used fresh water with a volume of 7 liters/tank. The results showed that treatment C provided the best results for absolute weight growth of 9-12 cm Sangkuriang catfish, at 8,8 grams per fish. Water quality data showed a water temperature of 27.8-28.8°C, pH of 6.36-6.60, and dissolved oxygen of 5.60-5.75 ppm.